Some Origins of Singularity of thought and Social Conformity (Global Journal of Human-Social Science, 2014)
Louis Althusser suggested eight forms of ideology which comprise the Ideological State Apparatuses (ISA). According to Althusser these ISA's manage hegemony without the need for the state repressive force. This original effort suggests that in the wake of massive historical and social change, two additional ideologies must be added to Althusser concepts; a) the Mass Culture Ideology; and b) "Technological Nihilism". Indeed, both ideologies operate in tandem with each other resulting in the singularity of thought, social conformity, and hegemony.